2014
DOI: 10.1186/1478-811x-12-31
|View full text |Cite
|
Sign up to set email alerts
|

Internal translation of the connexin 43 transcript

Abstract: BackgroundConnexin 43 (Cx43), the most widely expressed gap junction protein, is associated with a number of physiological and pathological conditions. Many functions of Cx43 have been shown to be independent of gap junction formation and only require the expression of Cx43 C-terminal fragments. Recent evidence demonstrated that naturally occurring C-terminal isoforms can be generated via internal translation.FindingsHere, we confirm that C-terminal domains of Cx43, particularly the major 20-kDa isoform, can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 25 publications
4
87
0
Order By: Relevance
“…This is the first evidence that alternative translation is possible for human ion channels and in human heart. These results have since been supported by a separate report showing that the GJA1–20k isoform is expressed in many cell lines that express high levels of full length Cx43 57 . In addition, it has also been reported that this 20 kDa isoform is induced by hypoxic stimuli in the mouse brain and is the result of internal translation from an IRES element 58 .…”
Section: Regulation Of Cx43 Forward Trafficking By Its Alternatively supporting
confidence: 55%
“…This is the first evidence that alternative translation is possible for human ion channels and in human heart. These results have since been supported by a separate report showing that the GJA1–20k isoform is expressed in many cell lines that express high levels of full length Cx43 57 . In addition, it has also been reported that this 20 kDa isoform is induced by hypoxic stimuli in the mouse brain and is the result of internal translation from an IRES element 58 .…”
Section: Regulation Of Cx43 Forward Trafficking By Its Alternatively supporting
confidence: 55%
“…Gap junction assembly by connexin 43 was documented to propagate cell-killing signals initially generated by a single cell spontaneously initiating apoptosis to surrounding cells in a bladder carcinoma cell line [40]. Since the expression of connexin 43 is regulated by the PI3K/AKT/mTOR and Mnk1/2 pathways [41], the role of ASC in gap junction signaling that occurs at a high density needs to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Cx43 is the first mammalian ion channel shown to be subjected to alternative translation, which has already been confirmed by two separate reports [38, 39]. It has also been found that the 20 kDa isoform (GJA1-20K) assists with Cx43 forward trafficking.…”
Section: Trafficking In Healthy and Diseased Heartsmentioning
confidence: 56%
“…Given the recent findings of alternative translation of smaller Cx43 isoforms, which facilitate the forward trafficking of full length Cx43, and the increases in such alternative translation by inhibiting mTOR and Mnk1/2 [37, 39], use of existing mTOR and Mnk1/2 inhibitors could increase plaque density. As mTOR inhibitors are already widely used in the fields of organ transplant and immunosuppression, therapeutic rescue could potentially be available as a novel use of an existing agent.…”
Section: Pharmacologic Rescue Of Trafficking Pathwaysmentioning
confidence: 99%